Emergency frequency control method for high-proportion renewable energy power system under low inertia - Luo, Guan; Chen, Jinli; Liu, Ming; Xiao, Yan; Li, Xiong (Journal of power technologies, 2024)
In a new energy power system, there is a lack of sufficient inertia support when facing sudden frequency disturbances, which threatens frequency stability. To address the problem of how to control the frequency of a high-proportion new energy power system under low inertia, this paper proposes an emergency frequency control method based on the idea of control and cutting coordination to reduce the frequency deviation of the power system. With the minimization of the power system frequency offset and the minimization of the control cost as the objective function and the minimum inertia and power balance of the power system as the constraint conditions, an emergency frequency optimization control model of a high-proportion new energy power system under low inertia is established. Solving the model obtains the minimum frequency offset and the minimum control cost, and the optimal cutting and load reduction strategy is effectively determined to achieve stable control of the power system frequency. Results show that under different power shortage conditions, this method can effectively determine the inertia of the power system, thereby completing the control of the emergency frequency of the power system. Through the control of this method, the maximum frequency deviation of the power system is maintained at about 0.6 Hz, and the maximum total control cost is 16,600 CNY. Compared with the situation before the application of this method, the frequency deviation and control cost of the power system are significantly reduced, that is, the emergency frequency control effect of this method is better. The research conclusions are of great technical help in maintaining the safe and stable operation of the power system.